Productivity and quality of spring barley varieties in the eastern part of the Rostov region - A. V. Alabushev; V. A. Yatsenko; A. S. Popov; G. P. Gerasimenko; A. A. Dontsova (Зерновое хозяйство России)
A.V. Alabushev, Doctor of Agricultural Sciences, professor, academician of RAS; V.A. Yatsenko, leading research associate; A.S. Popov, Candidate of Agricultural Sciences, leading research associate; G.P. Gerasimenko, Candidate of Agricultural Sciences, leading research associate; A.A. Dontsova, Candidate of Agricultural Sciences, leading research associate FSBSI “Agricultural Research Center ‘Donskoy” (347740, Zernograd, Nauchny Gorodok, 3; email: vniizk30@mail.ru) Productivity and quality of spring barley varieties in the eastern part of the Rostov region The choice of the variety is one of the main methods to increase productivity of spring barley. The trials were carried out by the associates of the laboratory of the cultivation technologies of grain crops on the experimental fields of OOO ‘Niva’ in the Orlov district of the eastern part of the Rostov region. The experiments were conducted on dark chestnut soil of medium power and weak alkalinity. According to granule content the soils were heavy loam with 60-75% of physical clay, with medium content of mobile phosphorus and exchangeable potassium. The content of humus in the layer of 0-20 cm ranges from 2.5 to 3.1%. The object of the study were the spring barley varieties ‘Priazovsky9’, ‘Ratnik’, ‘Zhedry’, ‘Leon’, ‘Novik’, ‘Gris’ and ‘Yula’ developed in FSBSI ARRIGC named after I.G. Kalinenko. The study was carried out during the years of 2012-2015, which were different in moisture supply. The 2012 agricultural year was dry; the 2014 and 2015 agricultural years were more favorable, due to the amount of precipitation, so the productivity of the crop significantly ranged during the studied years. The varieties ‘Gris’ (2.15t/ha), ‘Priazovsky9’ (2.06t/ha) and ‘Ratnik’ (2.05t/ha) formed the largest yields on average during the years of study. The varieties ‘Novik’ (12.73%), ‘Leon’ (12.34%) and ‘Ratnik’ (12.31%) showed the largest content of protein in kernels. The varieties ‘Priazovsky9’ (41.3g), ‘Ratnik’ (41.2g) and ‘Gris’ (40.6g) possessed the largest index of the trait ‘1000-kernel weight’.